2024
DOI: 10.1088/2043-6262/ad2c7b
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and green synthesis of gold nanoparticles for mRNA delivery in vitro

Jeaneen Venkatas,
Moganavelli Singh

Abstract: Nanotechnology has paved the way for novel treatment strategies for diseases such as cancer. While chemical synthesis of nanoparticles (NPs) can introduce toxic and expensive reducing reagents, green synthesis offers an alternative with dual reducing and capping properties. Curcumin exhibits favourable pharmacological properties, enabling synergism with the therapeutic cargo. This study aimed to compare green and chemically synthesised gold NPs for the delivery of FLuc-mRNA in vitro. Chemical and green synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Synthesis of AuNPs using citrate reduction remains an attractive and reliable method of preparation that uses water and no additional passivating ligand. A recent study revealed that there was very little difference between green and chemical synthesis with regard to gene delivery [33]. CS was used to modify the AuNPs for better stability and for its ability to bind electrostatically to the anionic pDNA via its cationic amine groups.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of AuNPs using citrate reduction remains an attractive and reliable method of preparation that uses water and no additional passivating ligand. A recent study revealed that there was very little difference between green and chemical synthesis with regard to gene delivery [33]. CS was used to modify the AuNPs for better stability and for its ability to bind electrostatically to the anionic pDNA via its cationic amine groups.…”
Section: Discussionmentioning
confidence: 99%